2018
DOI: 10.1021/acssuschemeng.7b04390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coproduct Uses on Environmental and Economic Sustainability of Hydrocarbon Biofuel from One- and Two-Step Pyrolysis of Poplar

Abstract: This study investigated the environmental and economic sustainability of liquid hydrocarbon biofuel production via fast pyrolysis of poplar biomass through two pathways: a one-step pathway that converted poplar via fast pyrolysis only, and a two-step pathway that includes a torrefaction step prior to fast pyrolysis. Optimization of these fast pyrolysis-based biofuel processes were investigated through heat integration and alternative uses of the coproduct biochar, which can be sold as an energy source to displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…With the growing push for renewable and sustainable manufacturing, the under-utilization of lignin is becoming increasingly difficult to ignore.T he value of lignocellulosicb iomass as af eedstocki sc urrently dominated by cellulose, the only component recovered in ap ulp mill and the key component of interest in ab ioethanol refinery.U nfortunately,o ver 99 %o ft he lignin generated in these facilities is not recovered, but is simply burned for its heatingv alue. [1] However,i fl arge-scale, higher-value applications for the lignin byproduct could be identified, the economic viability of biorefineries (for paper or ethanol) would be enhanced significantly.F or example, as demonstrated in recent techno-economic analyses, the conversion of lignin into higher-valueb iochemicals [2,3] or its valorization into precursors for polymers and materials applications [4][5][6] can reduce the price of bioethanol from lignocellulosic biomass to wellbelow the DOE goal [7] of $3/gallon gasoline equivalent. Nevertheless, lignin has thus far provent ob ed ifficult to valorize.T wo properties of lignin that need to be controlled, if lignin is to achieve its potential as ar enewable biopolymer,are its purity and its molecular weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing push for renewable and sustainable manufacturing, the under-utilization of lignin is becoming increasingly difficult to ignore.T he value of lignocellulosicb iomass as af eedstocki sc urrently dominated by cellulose, the only component recovered in ap ulp mill and the key component of interest in ab ioethanol refinery.U nfortunately,o ver 99 %o ft he lignin generated in these facilities is not recovered, but is simply burned for its heatingv alue. [1] However,i fl arge-scale, higher-value applications for the lignin byproduct could be identified, the economic viability of biorefineries (for paper or ethanol) would be enhanced significantly.F or example, as demonstrated in recent techno-economic analyses, the conversion of lignin into higher-valueb iochemicals [2,3] or its valorization into precursors for polymers and materials applications [4][5][6] can reduce the price of bioethanol from lignocellulosic biomass to wellbelow the DOE goal [7] of $3/gallon gasoline equivalent. Nevertheless, lignin has thus far provent ob ed ifficult to valorize.T wo properties of lignin that need to be controlled, if lignin is to achieve its potential as ar enewable biopolymer,are its purity and its molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…However, if large‐scale, higher‐value applications for the lignin byproduct could be identified, the economic viability of biorefineries (for paper or ethanol) would be enhanced significantly. For example, as demonstrated in recent techno‐economic analyses, the conversion of lignin into higher‐value biochemicals or its valorization into precursors for polymers and materials applications can reduce the price of bioethanol from lignocellulosic biomass to well below the DOE goal of $3/gallon gasoline equivalent. Nevertheless, lignin has thus far proven to be difficult to valorize.…”
Section: Introductionmentioning
confidence: 99%
“…Fast pyrolysis is a thermochemical process of biomass liquefaction by optimizing pyrolysis conditions including temperature, heating rate, and vapor resident time . It offers a promising approach to convert biomass to renewable biofuels to replace fossil fuels for environmental benefits. On the other hand, the economic analysis has shown difficulty in achieving its economic feasibility due to the selling prices being uncompetitive with petroleum-derived fuels. Previous studies suggested that the aqueous fraction of the pyrolysis liquid created a costly wastewater treatment burden for the conversion process. , Therefore, the valorization of the pyrolysis aqueous liquid can improve the economic performance of the biomass pyrolysis process. This aqueous liquid produced from woody biomass pyrolysis is referred to as liquid smoke, smoke condensate, wood vinegar, and pyroligneous acid in different research areas.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,15,12,16 Coproduct selection will impact the final fuel MSP. 17 Pretreatment of lignocellulosic biomass is often complex and expensive. This process must disrupt the natural crystalline structure to facilitate enzyme access to cellulose and hemicellulose for saccharification.…”
Section: Introductionmentioning
confidence: 99%